Пам’ятки археології села Ременів - Конопля, В.; Оприск, В. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
This article deals with preliminary results of archaeological surveys on the territory near Remeniv village (Kamianko-Buz’kyi district, L’viv region) during 1996. This work was carried out by Regional inspection service for preservation of monuments of archaeology. Obtained data demonstrate process of inhabitation of this area from Eraly Iron Age till the beginning of Old Russian period. Important part of this complex presents a group of settlements of Cherniakhiv culture.